Handbook of creativity - Sternberg, Robert J. (Cambridge Cambridge University Press, 1999)
The goal of the Handbook of Creativity is to provide the most comprehensive, definitive, and authoritative single-volume review available in the field of creativity. To this end, the book contains 22 chapters covering a wide range of issues and topics in the field of creativity, all written by distinguished leaders in the field. The chapters have been written to be accessible to all educated readers with an interest in creative thinking. Although the authors are leading behavioral scientists, people in all disciplines will find the coverage of creativity divided in the arts and sciences to be of interest. The volume is divided into six parts. Part I, the Introduction, sets out the major themes and reviews the history of thinking about creativity. Subsequent parts deal with methods, origins, self and environment, special topics and conclusions.